2012
DOI: 10.7314/apjcp.2012.13.1.309
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Psychological Characteristics in Patients with Hepatic Malignancy before Interventional Procedures

Abstract: Objective: To investigate the psychological characteristics of hepatic malignancy patients before interventional procedures and assess associations with related factors. Methods: Two hundred and thirteen patients requiring interventional procedure for hepatic malignancy were asked to complete a survey of health knowledge and psychological symptom on health knowledge questionnaire and SCL-90 before interventional procedure. Logistic regression analysis was employed to determine the association of various demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“… 13 , 15 , 16 Owing to lack of the information of disease or interventional procedures, diagnostic and therapeutic procedures performed in the interventional radiology department are anxiety provoking and painful for some patients. Wang et al 14 surveyed 213 patients requiring interventional procedure for hepatic malignancy and confirmed that the health knowledge is associated with the psychological symptoms of the patients. In the study, the pain score in the HE group was significantly lower than that in the control group.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“… 13 , 15 , 16 Owing to lack of the information of disease or interventional procedures, diagnostic and therapeutic procedures performed in the interventional radiology department are anxiety provoking and painful for some patients. Wang et al 14 surveyed 213 patients requiring interventional procedure for hepatic malignancy and confirmed that the health knowledge is associated with the psychological symptoms of the patients. In the study, the pain score in the HE group was significantly lower than that in the control group.…”
Section: Discussionmentioning
confidence: 94%
“…Health knowledge was assessed with HKQ, a questionnaire created for HCC patients before interventional procedure. 14 The HKQ consists of patient’s name, ID, and five questions defining a total score from 0 to 10 ( Table 1 ). Every answer is evaluated and rated on a scale of 0–2: “0”, do not know; “1”, knows but the answer is incomplete; and “2”, know and the answer is complete.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Z. X. Wang et al, 2012). The SCL-90 questionnaire test is the questionnaire survey that is used for evaluating comprehensive mental health and has good validity and reliability.…”
Section: Discussionmentioning
confidence: 99%